PENGGUNAAN APLIKASI MANAJEMEN REFERENSI DALAM MEMBUAT KARYA TULIS ILMIAH - Muhammad Taufiqurrahman; Ahmad Ridani; Sudadi; Bahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Information technology advancements demand systematic reference management to maintain academic integrity. This study aims to examine the role of reference management applications in enhancing the efficiency and quality of scientific writing. Employing a library research method with content analysis, the study evaluates literature regarding the use of software such as Mendeley, Zotero, and EndNote. The results indicate that these applications facilitate metadata organization, automated citations (APA, MLA, IEEE), and the prevention of accidental plagiarism. Integration with word processors significantly improves bibliography accuracy and researcher productivity. The study concludes that utilizing this technology is a crucial necessity in the modern academic world to ensure consistency and professionalism. Using these tools not only simplifies technical aspects but also strengthens the intellectual depth of scientific work.